Hoverflies (Diptera: Syrphidae) as biodiversity indicators for assessing urban forest habitats - De Groot, Maarten (Acta silvae et ligni, 2022)
Urban and peri-urban forests are important habitats for maintaining biodiversity in cities. In this paper, we report a method for using hoverflies as biodiversity indicators in urban forest habitats. As a case study, forest habitats in three peri-urban and urban forests were assessed and compared to rural forests in Slovenia. Rožnik (Ljubljana) was chosen as the urban forest site, Mestni log (Ljubljana) and Brdo (Kranj) were chosen as the peri-urban sites, and eight sites were chosen in rural forests in different ecoregions in Slovenia. Forest hoverfly species richness and the species composition of different biological traits were compared between the peri-urban forests, urban forest and rural forest sites. In addition, species richness was assessed for changes in response to weather conditions between years. The number of species with the investigated traits in the urban and peri-urban forests was within the range of the number of species observed in the rural forests. The number of saproxylic species was higher in the urban forest but lower in the peri-urban forests compared to the rural forests. The proportions of species with different feeding modes and different development times were similar between the peri-urban, urban and rural forests. The proportions of species with development times of less than 2 months or more than 1 year and of predatory species were similar in the urban and peri-urban forests but higher in the rural forests. The species composition of the other biological traits differed between the peri-urban, urban and rural forests. Species richness and abundance displayed large differences in phenological patterns between 2012 and 2013; these differences are related to differences in the minimum temperature for these years. The results are discussed in relation to forest management in urban forests, the usefulness of hoverflies as a biodiversity indicator and possible extrapolation to other species groups.
Keywords: biological traits; biološke lastnosti; ecosystem services; ekosistemske storitve; forest management; gospodarjenje z gozdovi; mestni gozdovi; muhe trepetavke; saproksilne vrste; saproxylic species; Syrphidae; urban forest